2011
DOI: 10.1016/j.jss.2010.10.014
|View full text |Cite
|
Sign up to set email alerts
|

A Clinically Applicable Porcine Model of Septic and Ischemia/Reperfusion-Induced Shock and Multiple Organ Injury

Abstract: Background-Although many sepsis treatments have shown efficacy in acute animal models, at present only activated protein C is effective in humans. The likely reason for this discrepancy is that most of the animal models used for preclinical testing do not accurately replicate the complex pathogenesis of human sepsis. Our objective in this study was to develop a clinically applicable model of severe sepsis and gut ischemia/reperfusion (I/R) that would cause multiple organ injury over a period of 48hrs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 46 publications
2
43
0
1
Order By: Relevance
“…-abdominal ischemia-reperfusion 1839 .......................................................................................................................... A pathologic animal model of septic and ischemia/reperfusion-induced shock and multiple organ injury replicated systemic inflammation and major organ system dysfunction seen in trauma patients and those with sepsis. 21 Similar to our findings, progressive functional deterioration within organs (including histopathologic injury to the lungs, kidney, liver, and intestines of the animals) occurred due to changes in hemodynamic status associated with shock. The pathologic porcine model constructed in the present study was developed according to the hypothesis of ischemia/reperfusion injury as it occurs in human patients.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…-abdominal ischemia-reperfusion 1839 .......................................................................................................................... A pathologic animal model of septic and ischemia/reperfusion-induced shock and multiple organ injury replicated systemic inflammation and major organ system dysfunction seen in trauma patients and those with sepsis. 21 Similar to our findings, progressive functional deterioration within organs (including histopathologic injury to the lungs, kidney, liver, and intestines of the animals) occurred due to changes in hemodynamic status associated with shock. The pathologic porcine model constructed in the present study was developed according to the hypothesis of ischemia/reperfusion injury as it occurs in human patients.…”
Section: Discussionsupporting
confidence: 89%
“…The evidence to prove the existence of Paneth cells in pigs remains controversial, which makes the study of regenerative events following reperfusion injury more complicated in pig model. 26 Also, domestic piglets may not have been the best choice of experimental animal since the majority of domestic piglets have pre-existing pulmonary infections, 20,21 which may have affected our results. In addition, the CO remained stable in our model, but the CVP increased gradually and significantly.…”
mentioning
confidence: 99%
“…We have employed a well-established translational porcine model of ARDS using gut ischemia reperfusion (I/R) injury and peritoneal sepsis (PS) induced by fecal clot implantation in large animals (18) and transferred genes four hours after injury. To our knowledge, this is the first time gene transfer has been used as therapy following injury (PS+I/R) in a clinically applicable large animal model suggesting this approach may have clinical therapeutic potential.…”
Section: Introductionmentioning
confidence: 99%
“…Kubiak et al, showed that the Multiple Organ Dysfunction Syndrome (MODS) comes from an alteration of the inflammatory cascade system where the source is a vicious circle with abdominal start (activation and release of physiological, cellular systems and chemical mediators triggered) that stars inflammation-damageinflammation, abdominal level first and then systemically [8].…”
Section: Introductionmentioning
confidence: 99%